Integrated management strategies increased silage maize yield and quality with lower nitrogen losses in cold regions - Li, Changqing; Tong, Bingxin; Jia, Mengyang; Xu, Huasen; Wang, Jiqing; Sun, Zhimei (Frontiers in Plant Science, 2024)
Introduction High-yield and high-quality production of silage maize in cold regions is crucial for ensuring the sustainable development of livestock industry. Methods This study first conducted an experiment to select the optimized silage maize varieties and densities using a split-plot design. The tested maize varieties were Xuntian 3171, Xuntian 16, Xunqing 858, and Fengtian 12, with each variety planted at densities of 67,500, 79,500, and 90,000 plants ha-1. Following the variety and density selection, another experiment on optimizing nitrogen management for silage maize was carried out using a completely randomized design: no nitrogen fertilizer (T1), applying urea-N 320 kg ha-1 (T2), applying urea-N 240 kg ha-1 (T3), applying polymer-coated urea-N 240 kg N ha-1 (T4), and ratios of polymer-coated urea-N to urea-N at 9:1 (T5), 8:2 (T6), 7:3 (T7), and 6:4 (T8). T5-T8 all applied 240 kg N ha-1. The yield and quality of silage maize, nitrogen use efficiency and balance, and economic benefits were evaluated. Results Results showed that Xunqing 858 had significantly higher plant height (8.7%-22.6% taller than the other three varieties) and leaf area (30.9% larger than Xuntian 3171), resulting in yield 11.5%-51.6% higher than the other three varieties. All varieties achieved maximum yields at a planting density of 79,500 plants ha-1. Integrated management strategy 7 (T7: Xunqing 858, 79,500 plants ha-1, polymer-coated urea-N to urea-N ratio of 7:3) achieved the highest yield of 73.1 t ha-1, a 6.1%-58.1% increase over other treatments. This strategy also produced the highest crude protein (11.1%) and starch (19.1%) contents, and the lowest neutral detergent fiber content (50.6%), with economic benefits improved by 10.3%-97.8% compared to other strategies. Additionally, T7 improved nitrogen use efficiency by 15.4%-94.5%, reduced soil nitrate leaching by 4.4%-36.5%, and decreased nitrogen surplus by 7.0%-46.6%. Conclusion and discussion Comprehensive analysis revealed that the integrated management strategy 7 significantly improved silage maize yield and quality in cold regions while enhancing nitrogen use efficiency and reducing the risk of nitrate leaching, aligning with green agriculture development requirements. These findings will provide vital theoretical insights and practical guidance for high-yield and high-quality silage maize production in cold regions worldwide.